1997
DOI: 10.1023/a:1005092601078
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Vibrations in microtubules and actin filaments are analysed using amethod similar to that employed for description of lattice vibrationsin solid state physics. The derived dispersion relations show thatvibrations in microtubules can have optical and acoustical branches.The highest frequency of vibrations in microtubules and in actinfilaments is of the order of 10(8) Hz. Vibrations are polar andinteraction with surroundings is mediated by the generatedelectromagnetic field. Supply of energy from hydrolysis of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…MTs also act as railways along which motor proteins move, 5,6 and form the moving cores of cilia and flagella. 7,8 Since mechanical properties of MTs are crucial to fulfill their role in various cellular functions, such as in cell division, cell motility, and intracellular transport, microtubule mechanics has been the topic of numerous recent theoretical and experimental research, especially those on mechanical vibration and wave propagation of microtubules, [9][10][11][12][13][14] and dynamics instability of microtubules. [15][16][17][18] In addition to various discrete methods of modeling, such as molecular mechanics or lattice models, continuum isotropic elastic beam models have been widely used to study rodlike mechanical behavior of microtubules, based on the concept of flexural rigidity of microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…MTs also act as railways along which motor proteins move, 5,6 and form the moving cores of cilia and flagella. 7,8 Since mechanical properties of MTs are crucial to fulfill their role in various cellular functions, such as in cell division, cell motility, and intracellular transport, microtubule mechanics has been the topic of numerous recent theoretical and experimental research, especially those on mechanical vibration and wave propagation of microtubules, [9][10][11][12][13][14] and dynamics instability of microtubules. [15][16][17][18] In addition to various discrete methods of modeling, such as molecular mechanics or lattice models, continuum isotropic elastic beam models have been widely used to study rodlike mechanical behavior of microtubules, based on the concept of flexural rigidity of microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…Penrose 82 related consciousness to the action of the cytoskeleton and to microtubules in particular. Generation of Fröhlich's polar vibrations in microtubules was proposed by Pokorný et al 30 The oscillations in the tubulin heterodimers in the microtubules interact with the ordered water and the free charges in the water inside the microtubule cavity that conditions the microtubule function. 32 The ordered water around microtubules provides low damping 49 and may also participate in the coherent oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…Large dielectrophoretic effects of the yeast cells in the M phase (when cells divide and the microtubule activity is high) were measured by Pohl et al 14 Tuszyński et al 29 proved that heterodimers in microtubules are electric dipoles. Generation of the electromagnetic field by microtubules based on Fröhlich's mechanism of the electrical polar vibrations was proposed by Pokorný et al 30 Electric oscillations measured at the cellular membrane of living yeast cells in the M phase display enhanced electric activity in some periods coinciding with mitotic spindle formation, metaphase, and anaphase A and B. 19 Disruption of microtubule polymerization in cells by an external electromagnetic field at the frequency 0.1-0.3 MHz suggests microtubule electromagnetic activity in heterodimer attachment.…”
Section: Oscillations In Microtubulesmentioning
confidence: 99%
“…The mechanisms generating both magnetic fields and acoustic waves in plants may be driven by similar biochemical processes within the cell, where nanomechanical oscillations of various components in the cytoskeleton can generate a spectrum of vibrations spanning from low kHz up to GHz 25,26 and even up to THz. 27 Specifically, Corsini et al 23 suggested that electrical currents and time-varying…”
Section: Acoustic and Magnetic Communication In Plantsmentioning
confidence: 99%